1992
DOI: 10.1016/0196-9781(92)90108-f
|View full text |Cite
|
Sign up to set email alerts
|

Galanin and calcitonin gene-related peptide immunoreactivity in nerves of the rat uterus: Localization, colocalization, and effects on uterine contractility

Abstract: Immunoreactivity to the neuropeptides galanin (GAL) and calcitonin gene-related peptide (CGRP) was examined in nerves in the rat uterus as a prelude to studying their effects on uterine contractility. With immunocytochemical techniques, GAL immunoreactivity (GAL-I) and CGRP-I were localized in myometrial nerves throughout the uterine horns and cervix, with nerves immunoreactive for CGRP being more numerous. Immunocytochemical double-labeling studies revealed GAL coexists with CGRP in a subpopulation of CGRP-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
1
27
2
Order By: Relevance
“…Shew et al (1992), while observing many fibers along blood vessels, reported more nonvascular CGRP-immunoreactive fibers than observed in our material. The role of uterine CGRP-immunoreactive fibers, and the possible distinction between the vascular and nonvascular CGRP-immunoreactive fibers, is unclear.…”
Section: Density and Patterns Of Innervation In The Virgin Ratcontrasting
confidence: 78%
See 1 more Smart Citation
“…Shew et al (1992), while observing many fibers along blood vessels, reported more nonvascular CGRP-immunoreactive fibers than observed in our material. The role of uterine CGRP-immunoreactive fibers, and the possible distinction between the vascular and nonvascular CGRP-immunoreactive fibers, is unclear.…”
Section: Density and Patterns Of Innervation In The Virgin Ratcontrasting
confidence: 78%
“…We would not have expected to find preganglionic efferent axons in the body of the uterus, and these would have been the only source of efferent CGRP-immunoreactive fibers. Indeed, Shew and coworkers (Shew et al 1991(Shew et al , 1992 reviewed the evidence that CGRP-immunoreactive fibers in the uterus are restricted to axons of primary afferent neurons, and they found it convincing.…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…SP contracts the smooth muscle of the myometrium and dilates uterine blood vessels Traurig and Papka, 1993). CGRP relaxes myometrial smooth muscle (Shew et al, 1990(Shew et al, , 1992Traurig and Papka, 1993) and myometrial contractions in the uterus of rats and humans are inhibited by CGRP Yallampalli et al, 2002;Gangula et al, 2003). CGRP is also a vasodilator of uterine vasculature (Gangula et al, 2003;Mowa et al, 2003).…”
Section: Sensory Innervation Of the Nonpregnant Rat Uterusmentioning
confidence: 95%
“…Since NKA-containing ®bres innervate the uterus of various species (Gibbons et al, 1985;Shew et al, 1992;Traurig et al, 1988), it can be postulated that NKA might have a role in the regulation of the uterine function, especially in pregnancy. This speculation is supported by the following reports: (1) The pelvic neurectomies lead to uterine dystocia in the pregnant rat (Higuchi et al, 1987;Traurig et al, 1984;, and aerent C-®bres may play a role in the neural regulation of parturition (Traurig et al, 1991); (2) NKA induced contractions in the rat myometrial strips (Fisher & Pennefather, 1997;Fisher et al, 1993;Pennefather et al, 1993) and (3) NK-2 receptor, which is preferentially activated by NKA, were predominant in the estrogen-primed rat myometrium (Fisher & Pennefather, 1998;1999;Fisher et al, 1993;Magraner et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%